(untitled) (Research, Society and Development, 2022)
This study aims to identify evidence of the performance of the nurse in mental health care from the beginning of pregnancy to the puerperium, the main related problems and risk factors, according to the exploratory and qualitative study conducted through bibliographic research. The research was carried out through studies available in the Virtual Health Library (VHL-BIREME), in the databases Latin American and Caribbean Literature on Health Sciences (LILACS) and in the Scientific Electronic Library Online (SCIELO) portal. The research took place from November 2021 to January 2022. The articles were published between the last ten years (2011 to 2020), and were written in the Portuguese. Six articles that met the inclusion criteria were selected and analyzed. The data were analyzed descriptively. The study identified the predisposing factors for the development of the Mental Health of pregnant women with a new look about the importance of nursing care. Pregnancy and the puerperium are critical phases in female life, since they promote several biopsychosocial transformations, contributing to the development of mental disorders, if a reception and support network is not offered to pregnant women. Nursing professionals should be available to listen to patients with a welcoming posture, which is the most important requirement of prenatal care within preventive action, thus being able to adequately direct pregnant women during continuous and humanized prenatal care.